ChemInform Abstract: Heterometallic Clusters [CuSn3S9]5‐ and [Cu6Sn6S20]10‐: Solvothermal Synthesis and Characterization of 4f—3d Thiostannates. Issue 40 (12th September 2013) - Chen, Ruihong; Wang, Fang; Tang, Chunying; Zhang, Yong; Jia, Dingxian
Abstract Compounds (IV), (VI), and (VIII) are characterized by XRD and UV/VIS reflectance spectroscopy.